(3OjhGf UGdM GdbRhjfjs - (3UGdM Hf egOj Hf QVG Hf eMeO Ydj GdMSjfj GdbRhjfj GdHZOGOjs ((3eMeO WGgQ GdSeGhj s)
(3ChdgG (B:s
(3bGd eGOMkG Ydj HGTG hGdj HZOGO dCeQ EbJVGg GdMGd MjG GdSgGO eYGgO GdRhQGA hLQi GdfSje HgG eY GdCfhGA s
(3BNQgG (B:s
(3hbGd ddSjO YjSi Hf GdSjO eMeO Ydj GdMSfj GdHZOGOj(B: (3CHG YjSi hef HCHjg YjSi cehSi bO CYGO GdejJ MjG LeYJ eQGYjG HOA GdeYGdj ceG LeYhG acfJ dgG MQjkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3GfXQ eY GdOQQ GdZQhjI aj eOGFM heQGKj GdYJQI GdeUWahjI GdOQQ GdZQhjI gPG gh GdcJGH GdChds
(3jdj GdOjhGf edMb aj CQHY hQbGJs
(3hoeQJH Ydi MQha GdeYLes
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs